2022
DOI: 10.1021/acs.biomac.1c01616
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Triggered the Quick Self-Assembly of Gallic Acid into Therapeutic Hydrogels for Healing of Bacterially Infected Wounds

Abstract: Programing self-assembly of naturally bioactive molecules has been a wide topic of great significance for biomedical uses. Despite the fact that plant-derived polyphenols with catechol or pyrogallol moieties have been widely studied to construct nanocomplexes or nanocoatings via self-polymerization, there is no report on the self-assembly of these polyphenols into therapeutic hydrogels for potential applications. Here, we reported that adding a very small amount of resveratrol (Res) into the gallic acid (GA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…After ultrasonic treatment and cooling to room temperature, the mixed solution spontaneously formed the GAS hydrogel. The GA hydrogel was obtained according to our previous reports. ,, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After ultrasonic treatment and cooling to room temperature, the mixed solution spontaneously formed the GAS hydrogel. The GA hydrogel was obtained according to our previous reports. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The GA hydrogel was obtained according to our previous reports. 40,41,46 Characterization of the GAS Hydrogel. The microstructure of the GAS hydrogel was observed using cold field emission scanning electron microscopy (cryo-SEM, SU8010/PP3010T, Japan).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have established the effectiveness of hydrogel embodiment with gallic acid in wound healing. Topical application of such gallic acid nanovesicle speeds up wound regeneration and demonstrated to downregulate the expression of inflammatory cytokines [ 124 , 125 ]. Caffeic acid conjugated on nanofiber nanovesicle, formed with PCL and CH, ameliorated its delivery on fibroblast neonatal cell line (NHDF-neo) [ 126 ].…”
Section: Designed Polyphenolic-loaded Nanocarriers For Inflammation-m...mentioning
confidence: 99%
“…RSV, a natural plant extract, has been shown to have antimicrobial properties and its antimicrobial activity may be due to disruption of cell membrane potential or blockage of DNA synthesis. In one study, RSV was found to be antibacterial against both bacterial and fungal infections [ 66 ]. However, compared to S. aureus and P. aeruginosa , RSV did not hinder the growth of C. albicans although it also inhibited it better, which means that the inflammatory response is stronger in fungal infections than in bacterial infections.…”
Section: Mechanisms Underlying the Beneficial Effects Of Rsv On Wound...mentioning
confidence: 99%